Developing Peer Participation Academic Supervision Model on Sociology Teachers of Senior High Schools in Pekalongan Regency - Suprihatini, Noerhidayah; Hardyanto, Wahyu; Masrukan, Masrukan (Educational Management, 2019)
The development peer participation academic supervision model is a supervision model which involves teacher supervisor by empowering the peers who have a task to give facilitation, guidance, and academic assistance in carrying out the supervision. This research aims to analyze and describe the implementation of academic supervision (initial model), develop academic supervision model based on teachers’ need, and examine the practicality of supervision model which is being developed. This Research and Development divided into three steps namely preliminary, development, and evaluation. Techniques for collecting the data are using interview, document analysis, and observation. The validity testing is using source triangulation. Preliminary stage is including literaiteraturery studies, field studies related to the problem that will be solved, and description and analysis of field’s finding. Development stage involves experts and practitioners, so resulting in a model that is ready to be tried out. Evaluation stage (limited trial) is using a design sheet to find out the practicality of the model. Results of the research (1) the implementation of academic supervision is less effective recently, (2) academic supervision that is appropriate to the teachers’ need is peer participation academic supervision which involves supervisors, the peers, and the teachers who are supervised from the planning stage to the follow-up stage, (3) the result shows that the academic supervision model is practical and statistically effective.